Pandemia em (dis)curso: ethé discursivos do jornal Folha de S. Paulo em manchetes e chamadas sobre Influenza A (H1N1) - Costa, Felipe de Souza [UNIFESP] (2016)
This paper aims to analyze the constitution of the discursive ethos of Folha de S. Paulo news-paper from headlines and whose theme is linked to the "Swine Flu" or Influenza A (H1N1). It is justified because it invests in a research that discusses the relation between media, discourse and public health. We come ourselves to the French Discourse Analysis, and to achieve this goal, we inscribe our discussions in the studies of Dominique Maingueneau (1997, 2008, 2010 and 2011). Our initial hypothesis was that the discursive ethos of Folha de S. Paulo showed up as scientific one and that there was a sense of pendulum invested in the first page set design that would go from panic to the containment. We select, based on a consultation in the newspaper database, the headlines and texts in the period from April to December 2009, and the criterion was that they should be related to the theme of "flu". In discussions of the results, we invest in these categories of analysis: discursive ethos, scenes of enunciation, global semantic and discursive formula. Finally, this research shows that, with regard to discursivization of the flu, Folha not only builds an ethos, scientific or objective, but reveals the presence of others as those of educational character and the servility, both in addition to the scientific. This investment in panic senses and restraint is showed by numbers, when Folha supposedly intends to "inform" the public, while the other "teaches" how to avoid transmission and detect the presence of disease in the infected body. In the middle of these two ethé, we have the ?servile?, indicted in the header through the slogan which contributes to the Maingueneau assumption (2013): the ethos is floating and, in the same time, plurivocal.